The role of Taxotere in adjuvant therapy for early breast cancer - I. V. Kolyadina; I. V. Poddubnaya (Опухоли женской репродуктивной системы)
In the present review has described the historical stages of systemic therapy of breast cancer with the use of taxanes, and has given a detailed description of drugs (paclitaxel and docetaxel). The role of docetaxel (Taxotere) in reducing the recurrences and death from cancer risk has shown. The major randomized trials has described; was studied the effectiveness of combination with docetaxel (Taxotere) in the adjuvant treatment of early breast cancer with or without lymph nodes involvement. The important role of docetaxel (Taxotere) in the adjuvant treatment of HER2-positive breast cancer was shown.